2016
DOI: 10.2196/resprot.6610
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Multicenter, Randomized Phase II Study to Evaluate the Efficacy and Safety of Eculizumab in Patients with Guillain-Barré Syndrome (GBS): Protocol of Japanese Eculizumab Trial for GBS (JET-GBS)

Abstract: BackgroundGuillain-Barré syndrome (GBS) is an immune-mediated neuropathy that causes acute flaccid paralysis. Immunoglobulin and plasma exchange are established treatments for GBS; however, a substantial number of patients, particularly those with severe disease, have poor recovery and residual deficits. Recent studies suggest that complement activation plays a pivotal role in GBS-associated axonal degeneration, and eculizumab is a humanized monoclonal antibody that specifically binds to complement component 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In addition, development of new therapeutic options, such as complement inhibition, may be needed for patients with poor prognosis. This issue is now under investigation (Yamaguchi et al, ; Davidson et al, ) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, development of new therapeutic options, such as complement inhibition, may be needed for patients with poor prognosis. This issue is now under investigation (Yamaguchi et al, ; Davidson et al, ) .…”
Section: Discussionmentioning
confidence: 99%
“…Based on these, a phase II clinical trial was conducted to investigate the safety and efficacy of eculizumab, humanized monoclonal antibody to complement C5, for the acute phase of GBS in Japan (Table 1). It enrolled 34 patients with GBS who cannot walk independently within 14 days from the onset 26,27 . Patients were randomly assigned (2:1) to IVIG plus eculizumab (900 mg) or placebo, which were administrated for 4 weeks 26 .…”
Section: Complement Inhibition In Gbs Patientsmentioning
confidence: 99%
“…It enrolled 34 patients with GBS who cannot walk independently within 14 days from the onset 26,27 . Patients were randomly assigned (2:1) to IVIG plus eculizumab (900 mg) or placebo, which were administrated for 4 weeks 26 . The primary endpoint was efficacy, the proportion of patients who restored the ability of walking independently (functional grade ≤ 2) at week 4, and safety 26 …”
Section: Complement Inhibition In Gbs Patientsmentioning
confidence: 99%
“…Eculizumab, a humanized monoclonal antibody that specifically binds to complement component 5 (C5) and potently inhibits generation of pro-inflammatory C5a and C5b-9 (implicated in axonal injury in GBS) is currently undergoing clinical trials in the United Kingdom and Japan to determine efficacy in GBS guided by prior animal model studies that demonstrated beneficial effects. 129,130 Other biologic agents are being proposed as potential future therapies based on animal model data or small case reports. 131 Due to the proposed pathogenic differences between demyelinating and axonal variants of GBS, future immunotherapy RCTs may require randomization based on electrophysiologic characterization or perform subgroup analyses dependent on relative numbers of these variants in addition to other demographic factors and measures of disease severity.…”
Section: Future Proposed Immunotherapiesmentioning
confidence: 99%